Prevalence of Fabry Disease in patients with left ventricular hypertrophy in Turkey: Multicenter study (LVH-TR subgroup analysis) - Güzel, Tuncay; Turhan Çağlar, Fatma Nihan; Ekici, Berkay; Kış, Mehmet; Öztaş, Selvi; Öz, Ahmet; Gök, Gülay; Kolak, Zeynep; Ergene, Asım Oktay (Springer, 2023)
Purpose: In this prospective study we aimed to determine the rate of Fabry Disease (FD) in patients with left ventricular hypertrophy (LVH), and to evaluate the clinical presentations of patients with FD in a comprehensive manner. In addition, we aimed to raise awareness about this issue by allowing early diagnosis and treatment of FD. Methods: Our study was planned as national, multicenter, observational. Totally 22 different centers participated in this study. A total of 886 patients diagnosed with LVH by echocardiography (ECHO) were included in the study. Demographic data, biochemical parameters, electrocardiography (ECG) findings, ECHO findings, treatments and clinical findings of the patients were recorded. Dry blood samples were sent from male patients with suspected FD. The ?-Gal A enzyme level was checked and genetic testing was performed in patients with low enzyme levels. Female patients suspected of FD were genetically tested with the GLA Gene Mutation Analysis. Results: FD was suspected in a total of 143 (16.13%) patients included in the study. The ?-Gal-A enzyme level was found to be low in 43 (4.85%) patients whom enzyme testing was requested. GLA gene mutation analysis was positive in 14 (1.58%) patients. Male gender, E/e’ mean ,and severe hypertrophy are important risk factor for FD. Conclusion: In daily cardiology practice, FD should be kept in mind not only in adult patients with unexplained LVH but also in the entire LVH population. Dry blood test (DBS) should be considered in high-risk patients, and mutation analysis should be considered in required patients.
Keywords: Fabry Disease; Left Ventricular Hypertrophy; Echocardiography; GLA Gene Mutation; a-Gal a Enzyme Activity